ChemInform Abstract: 3‐Substituted Prolines: From Synthesis to Structural Applications, from Peptides to Foldamers. Issue 20 (25th April 2013) - Mothes, Celine; Caumes, Cecile; Guez, Alexandre; Boullet, Heloise; Gendrineau, Thomas; Darses, Sylvain; Delsuc, Nicolas; Moumne, Roba; Oswald, Benoit; Lequin, Olivier; et al., et al.
Abstract Review: 78 refs.